THE POST-SECONDARY NETWORKED CLASSROOM: RENEWAL OF TEACHING PRACTICES AND SOCIAL INTERACTION - Campos, Milton; Laferrière, Thérèse; Harasim, Linda (Online Learning, 2001)
The application and use of telelearning technologies in post-secondary education is evolving from peripheral activities to central approaches. Educators are re-discovering collaborative education as they understand how electronic conferencing can support and empower teaching and learning. As students build knowledge collaboratively, asynchronous conferencing elevates engagement and participation, and increases thinking and understanding. This article presents the teaching practices of post-secondary educators who integrated asynchronous electronic conferencing in over one hundred mixed-mode courses at eight North American institutions between 1996 and 1999. Quantitative and qualitative research methods were applied to assess their practices and to further understand the correlation between the use of electronic conferencing and the degree of collaboration achieved. Based on the findings, pedagogical approaches for the use of electronic conferencing are provided, and are grouped according to the level of collaboration. As a result of this study, the authors present a suggested model for the networked classroom to foster and guide the transformation of pedagogical practice.